RESEARCH OF CONVERGENCE CONDITIONS OF THE MULTIPARAMETER OPTIMIZATION FUNCTIONAL OF TECHNOLOGICAL PROCESS OF MUNUFACTORING MAGNESITE REFRACTORY PRODUCTS - Zinovkin, V. V.; Mirnyi, V. J. (Radio Electronics, Computer Science, Control, 2015)
The conditions for the convergence of multi-parameter optimization of the functional process of preparation of magnesite refractory products were researched. It is shown that the signals of different physical nature is conveniently represented in the form of corresponding sets of parameters. Stable operation of multiparameter control is achieved by representing them as factors that allows more efficient implementation of this technique for the solution of engineering problems in the optimization of production lines with a set of parameters that characterize both the individual stages and the process as a whole. As other combinations lead to differ materially functional optimization and uncertainties. Along with the above, it is necessary to take into account the linear and non linear dependence between the analyzed parameters and their aggregate. The mathematical and computer models of optimal automated control multivariable process of preparation of magnesite refractory products. The simulation results are consistent with those obtained on a real production line in operation, which confirms the efficiency of the proposed method.